(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى تقييم مدى التزام الأندية الرياضية في الساحل السوري بتطبيق المنهج العلمي لعملية التحليل الاستراتيجي, حيث استعرض الباحث المراحل الرئيسة لعملية التحليل الاستراتيجي كمرحلة رئيسة من مراحل عملية التخطيط الاستراتيجي, وقام بتوزيع الاستبيان على رؤساء وأعضاء مجالس إدارات الأندية الرياضية في الساحل السوري والبالغ عددهم 42 فرد بغرض إجراء الدراسة الميدانية, وتم التوصل إلى مجموعة من النتائج والتوصيات تهدف إلى تحسين أداء الأندية الرياضية في مجال التحليل الاستراتيجي. This research aims at evaluate the commitment of sports clubs in the Syrian coast to apply the scientific method of the process of strategic analysis, the researcher reviewed the main phases of strategic analysis process as a key phase of the strategic planning process, and distributed the questionnaire to the heads and members of boards of sports clubs in the Syrian coast, a total number of 42, for the purpose of conducting the field study, and reached a set of conclusions and proposals aimed at improving the performance of sports clubs in the field of strategic analysis.